The Influence of salary and organizational culture on job satisfaction of iBox Palangka Raya Employees - Ferdinand, Ferdinand; Kristinae, Vivy; Mahrita, Ani; Toendan, Rita Yuanita; Tunjang, Hansly; Peridawaty, Peridawaty (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2025)
This study aims to analyze the influence of salary and organizational culture on employee job satisfaction at iBox Palangka Raya. Improving job satisfaction is important because it can positively impact employee effectiveness and loyalty, which are influenced by internal organizational factors. Therefore, a quantitative approach was used to examine the relationship between these variables. This study employed a quantitative descriptive method with the aid of SPSS version 23.0 software. The data used were primary data collected through questionnaires from 50 iBox Palangka Raya employees. The analysis showed that salary and organizational culture had a positive and significant influence of 63% on employee job satisfaction. This indicates that the better the salary structure and the stronger the organizational culture implemented, the higher the level of employee job satisfaction. These findings provide practical implications for iBox management to actively pay attention to the salary system and the development of organizational culture to create a conducive work environment. Future research is recommended to consider other variables, such as transformational leadership styles, to gain a more comprehensive understanding